PERBANDINGAN KETAHANAN PENYAKIT BULAI JENIS (Peronosclerospora Philippinensis dan Peronosclerospora Maydis) CALON VARIETAS JAGUNG HIBRIDA - suntoko, Suntoko; Christie , Chitra Dewi Yulia; Hendrayana, Febri; Lestari, Nia Agus (LPPM UNIVERSITAS KAHURIPAN KEDIRI, 2024)
This study aims to compare the resistance of hybrid maize varieties from